Examining the link among agility, knowledge management practices and firm performance : empirical evidence from electrical and electronics manufacturing firms - Ong, Eu Chin; Tan, Cheng Ling (Penerbit Universiti Kebangsaan Malaysia, 2021)
The study empirically investigates the relationship between agility and knowledge management practices on firm performance among the electrical and electronics manufacturing firms in Malaysia. The study was conducted using a survey method. A total of 85 manufacturing firms participated in this study. The findings showed that knowledge management practices mediate the relationship between agility and firm performance, which is in line with the Knowledge-Based View (KBV) where knowledge is an asset of the firm. The findings also empirically support the theoretical conceptualization of agility as co-dependent on knowledge management. The implications for practising managers within manufacturing firms are twofold, where agility alone does not lead to increased firm performance, and the implementation of only one of the factors is suboptimal.